A Citizen‐Centric Framework For Assessing E‐Government Effectiveness. Issue 1 (5th December 2017) - Sigwejo, Annastellah; Pather, Shaun
Abstract: In a quest to offer better services to both citizens and businesses throughout Africa, efforts to adopt e‐government projects are gaining momentum. As a result of this, there is a need for effective measurement of delivery and quality of such e‐services. Currently, there are several metrics applied to measure and rank the e‐readiness of various African countries. However, while these measures have provided a source of comparative analysis between different e‐government projects, they are far from being perfect. For example, most of these measures are diverse and difficult to compare, since they assume 'one size fits all' and ignore differing environmental, cultural and contextual factors of various countries. Further criticisms of these measures are that they are 'first generation metrics' designed for developed countries, as opposed to developing countries. This paper addresses the problem that there is a need for suitable evaluation strategies for understanding and measuring the effectiveness of e‐government services in order to improve the management thereof, and thereby attain the best possible value for citizens. The objective of this study was to investigate and develop a framework, for evaluating the effectiveness of e‐government services in a typical developing country. Tanzania was chosen as the context for this study: as a typical developing African country, its early phase of e‐government development provided an optimal case for this study concerned with the useful and effective evaluation of e‐government services. The findings indicate the key dimensions to consider when evaluating the effectiveness of e‐government services. These dimensions are synthesised into an e‐government citizen satisfaction framework (ECSF). The framework demonstrates how citizen and government imperatives should be amalgamated to evaluate the effectiveness of e‐government service. The findings further support the call to increase monitoring and evaluation of all ICT projects within government.